2005
DOI: 10.1016/j.otohns.2005.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tracheostomy on Well‐being and Body‐Image Perceptions

Abstract: This is the first report on tracheostomy related quality of life in noncancer patients conducted with specific psychological questionnaires.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
75
0
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 20 publications
0
75
0
5
Order By: Relevance
“…This is because there have been reports showing that tracheostomy has the potential to cause a significant decline in a patient's mental health, attributable to worsening self-esteem [12,14]. Therefore, if spine surgeons can present the possibility of later decannulation, patients would be more likely to accept subsequent therapy and the resulting situation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because there have been reports showing that tracheostomy has the potential to cause a significant decline in a patient's mental health, attributable to worsening self-esteem [12,14]. Therefore, if spine surgeons can present the possibility of later decannulation, patients would be more likely to accept subsequent therapy and the resulting situation.…”
Section: Discussionmentioning
confidence: 99%
“…The invasiveness secondary to tracheostomy is both physical and mental. It has been reported that there is a decline in a patient's mental health after tracheostomy, attributable to worsening self-esteem [12,14]. Therefore, it is important for patients to be aware about the possibility of decannulation, because this helps them to accept subsequent therapy and the resulting situation.…”
Section: Introductionmentioning
confidence: 99%
“…Tracheotomy and the facial scars resulting from extraoral devices or extraorally placed intraoral devices can have a significant psychological impact, leading to raised self-consciousness and anxiety levels 12,27 . The location of a submandibular scar in extraorally placed intraoral devices is considered to be less conspicuous.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term speech, behavior and developmental problems have been associated with tracheostomy as well as moderate to severe intellectual and physical impairments [14]. Adult studies have demonstrated reduced body image perception and reduced life satisfaction after long-term tracheostomy [15].…”
Section: Discussionmentioning
confidence: 99%